Comparing future projections of warm spells and their characteristics under climate change and stratospheric aerosol injection in CESM2 and UKESM1 - Glade, Ivy; Hurrell, James W.; Lombardozzi, Danica L. (Frontiers in Climate, 2025)
Extreme heat events have increased in frequency, intensity and duration over the last several decades as a result of anthropogenic climate change. Extreme heat events impact human and natural systems including human mortality and morbidity, agricultural and livestock yields, ecosystem vulnerability and water resource management. Increasing risks from climate change has prompted an increase in research into the potential impacts—both good and bad—of climate intervention. Stratospheric aerosol injection (SAI) is one of the most studied methods of climate intervention and could quickly cool or stabilize global temperatures by injecting reflective aerosols into the stratosphere. We investigate future projections of a type of extreme heat event, called a warm spell, in the context of a policy relevant and moderate emissions scenario (SSP2–4.5) and SAI deployment simulated in two Earth-system models: CESM2 and UKESM1. Warm spells are prolonged periods of anomalously high temperature that can occur at any time of the year. Under SSP2–4.5 warm spells are projected to become increasingly frequent, intense and longer in both models. SAI deployment is able to effectively mitigate many of these changes; however, differences in future projections of warm spells between CESM2 and UKESM1, regardless of whether or not SAI is deployed, highlight the importance of inter-model comparisons in assessments of future climates.